Comparison in Application of Active Learning Model The Power of Two and Everyone is Teacher Here to Improve Student Study Results on System of Human Motion subject in SMP Negeri 17 Banda Aceh - Kemala Sari; Khairil Khairil; Asiah MD (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2017)
This research purpose is to comprehend comparison in application of active learning model the power of two and everyone is teacher here to improve student study results on system of human motion subject in SMP Negeri 17 Banda Aceh. The approach in this research is a quantitative approach. Shape design of experiments in this research is a Pretest-Posttest Control Group Design. The data collection was held on June 9 to August 20, 2016. The sample in this study were students of class VIII-1 and VIII-2 , 29 students total for each class. VIII-1 using The Power Of Two model and VIII-2 using Everyone Is Teacher Here model. The data collection is done by giving the 25 items objective test with four alternative answers. Data collection was performed twice, before using one of the active learning model (pre-test) and after using one of the active learning model (post-test) in both experimental class.Test result of t N-Gain to α 0.05 in both classes obtained tcalculateis 2,46 while ttableis 1,68  which indicate that there are differences in student study result on System Of Human Motion subject that taught using active learning model The Power Of Two and active learning model Everyone Is Teacher Here.The conclusions of this research is that there is a difference of study result between students who are taught by active learning model The Power Of Two and  students who are taught by active learning model Everyone Is Teacher Here on System Of Human Motion subject in class VIII SMP Negeri 17 Banda Aceh.Key Words: The power of two, everyone is teacher here, Study Results